Initial Validation of the Weekly Calendar Planning Activity With Adolescents With ABI. (October 2022) - Doherty, Meghan; Dickerson, Dawn; Kadela, Kathryn; Noetzel, Michael; Wolf, Timothy J.; Berg, Christine; Dodd, Jonathan
The purpose of this study was to assess the validity of the Weekly Calendar Planning Activity Middle/High School (WCPA) in adolescents with acquired brain injuries (ABI). We recruited neurotypical controls ( n = 27) and adolescents with ABI ( n = 14) to complete a 90-min battery of cognitive tests. Adolescents with ABI were further divided into mild and severe groups by Glasgow Coma Scale Score and compared with controls. Mann–Whitney U tests revealed significant differences ( p = .05) on the WCPA between groups in total time to complete and rules followed. Between the controls and severe group, a significant difference ( p = .05) was found for total time spent, errors, rules followed, strategies used, and accurate appointments ( p = .01). Moderate correlations were found between the WCPA and neuropsychological tests (ρ = .31–.45). The WCPA is a valid performance-based assessment of functional cognition that can be used to detect deficits in adolescents with severe ABI.